2004
DOI: 10.1007/s00132-004-0737-x
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro- und In-vivo-Knochenregenerierung durch mesenchymale Stammzellen aus dem Nabelschnurblut

Abstract: Human USSC are a mesenchymal multipotent stem cell population that shows osteoblastic differentiation onto a collagen I/III carrier in vitro as well as in an athymic rat in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…In a study involving athymic rats, human UCB-MSCs displayed osteogenic differentiation in vitro , survived after xenotransplantation and differentiated into osteoblasts that filled the bony defects [10]. A recent study reported that human UCB-MSCs have a significantly stronger osteogenic potential but less capacity in adipogenic differentiation than bone marrow MSCs in vitro [4].…”
Section: Discussionmentioning
confidence: 99%
“…In a study involving athymic rats, human UCB-MSCs displayed osteogenic differentiation in vitro , survived after xenotransplantation and differentiated into osteoblasts that filled the bony defects [10]. A recent study reported that human UCB-MSCs have a significantly stronger osteogenic potential but less capacity in adipogenic differentiation than bone marrow MSCs in vitro [4].…”
Section: Discussionmentioning
confidence: 99%
“…MC3T3 osteoblastic cells were seeded on cell culture plastic as a reference an on the different materials at a cell density of 10.000 cells /cm 2 in alpha‐minimum essential medium with 10% FBS and 1% penicillin–streptomycin and cultivated for 8 days in 48‐well cell culture plates in a cell culture incubator at standard cell culture conditions (37°C; 100% humidity, and 5% CO 2 ). Cell activity was measured at the start of the culture (day 0) and on day 8 using an 3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium‐bromide (MTT)–enzyme‐linked immunoabsorbent assay cell culture test (Sigma–Aldrich) 26, 27. This in vitro test is based on the reduction of the yellow, water soluble tetrazolium salt to the blue‐violet colored formazan by metabolically active cells.…”
Section: Methodsmentioning
confidence: 99%
“…mesenchymaler Progenitorzellen (MPC) aus dem Nabelschnurblut intensiv wissenschaftlich erforscht [2,5,9]. So stellt nach Eblenkamp et al der Einsatz mesenchymaler Progenitorzellen zum gegenwärti-gen Zeitpunkt eines der spannendsten Felder der biomedizinischen Forschung dar [5].…”
Section: Introductionunclassified